Craniopharyngioma and epidermoid tumour in same child: a rare association. (3rd June 2013) - Singh, Deepak Kumar; Singh, Neha; Parihar, Anit; Singh, Ragini
Abstract : Simultaneous occurrence of histologically different primary brain tumours is rare, and its preoperative diagnosis is still challenging. The explanations for the simultaneous occurrence of different primary intracranial tumours in the absence of phacomatoses or prior radiation exposure are at present hypothetical, and these tumours could be simply coincidental. Herein, we report a case of a boy presenting with features of raised intracranial pressure and right-sided sensorineural hearing loss. Brain MRI revealed two different neoplastic pathologies at different sites: an intrasellar and suprasellar craniopharyngioma and a right cerebello-pontine angle epidermoid. To the best of our knowledge, this is the first report in literature of a craniopharyngioma coexisting with an epidermoid, in the same individual.